2021
DOI: 10.3390/diagnostics11122316
|View full text |Cite
|
Sign up to set email alerts
|

Pemafibrate Ameliorates Liver Dysfunction and Fatty Liver in Patients with Non-Alcoholic Fatty Liver Disease with Hypertriglyceridemia: A Retrospective Study with the Outcome after a Mid-Term Follow-Up

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease related to metabolic syndrome. No standard pharmacological treatment has yet been established. We retrospectively evaluated the efficacy of pemafibrate in 16 NAFLD patients (11 men and 5 women; median age, 59 years; range, 27–81 years) who had taken pemafibrate for at least one year. They were all diagnosed with fatty liver according to imaging and clinical criteria. They were administered pemafibrate from October 2018 to October 2021 (median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…For the first time, our study revealed that pemafibrate treatment led to a decrease in liver stiffness when assessed using SWE, however Nakajima et al reported that pemafibrate showed a significant reduction in liver stiffness using another instrument, magnetic resonance elastography, in a double-blind, phase 2 study in patients with NAFLD ( 11 ). We demonstrated that the change in liver stiffness was accompanied with a significant improvement in blood liver fibrosis markers such as Plt count and FIB-4 index, which was consistent with previous reports ( 11 , 15 , 17 , 18 , 21 ). The significant reduction in liver stiffness and fibrosis markers suggests an overall improvement in liver fibrosis, indicating that pemafibrate may have another advantage in treating patients with liver fibrosis, since liver fibrosis is associated with an increased risk of developing liver-related events and is predictive in NAFLD patient prognosis ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…For the first time, our study revealed that pemafibrate treatment led to a decrease in liver stiffness when assessed using SWE, however Nakajima et al reported that pemafibrate showed a significant reduction in liver stiffness using another instrument, magnetic resonance elastography, in a double-blind, phase 2 study in patients with NAFLD ( 11 ). We demonstrated that the change in liver stiffness was accompanied with a significant improvement in blood liver fibrosis markers such as Plt count and FIB-4 index, which was consistent with previous reports ( 11 , 15 , 17 , 18 , 21 ). The significant reduction in liver stiffness and fibrosis markers suggests an overall improvement in liver fibrosis, indicating that pemafibrate may have another advantage in treating patients with liver fibrosis, since liver fibrosis is associated with an increased risk of developing liver-related events and is predictive in NAFLD patient prognosis ( 29 ).…”
Section: Discussionsupporting
confidence: 92%
“…They also observed ameliorated FibroScan-AST score in 10 patients with NAFLD during PEM treatment, which correlated with ALT changes and demonstrated the hepatic anti-inflammatory effect of PEM [ 27 ]. Ikeda et al reported that PEM significantly decreased TG and ALT in 16 NAFLD patients, with fatty liver improvement in some cases [ 28 ]. Nakajima et al evaluated the efficacy and safety of PEM in 58 patients with NAFLD in a placebo-controlled study and found that while treatment for 18 months did not reduce liver fat content, it significantly decreased magnetic resonance elastography-measured liver stiffness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 As for previous studies of hepatic steatosis, Ikeda et al reported improvement in liver steatosis (39.1 ∓ 1.2 to 57.8 ∓ 2.7 HU, P = 0.028) and liver/spleen ratio (0.76 ∓ 0.04 to 1.18 ∓ 0.02, P = 0.012), but only three cases were included in the study. 23 Hatanaka et al showed no significant improvement in CAP using Fibroscan, 25 and Nakajima et al reported no evident improvement observed by MRI-PDFF. 14 Collectively, most studies to date have reported improvement in fibrosis/stiffness, but improvement in steatosis is not definitive when pemafibrate is used alone for fatty liver disease.…”
Section: Discussionmentioning
confidence: 97%
“…As for previous studies of hepatic steatosis, Ikeda et al . reported improvement in liver steatosis (39.1 ∓ 1.2 to 57.8 ∓ 2.7 HU, P = 0.028) and liver/spleen ratio (0.76 ∓ 0.04 to 1.18 ∓ 0.02, P = 0.012), but only three cases were included in the study 23 . Hatanaka et al .…”
Section: Discussionmentioning
confidence: 98%